Les Community arts en Grande-Bretagne : un mouvement artistique engagé, 1968-1990 - Mathilde Bertrand (Revue Française de Civilisation Britannique)
The community arts movement appeared in the United-Kindgom in the wake of the counter-culture of the 1960s. Inspired by artists from different disciplines, community arts practices aimed at giving access to artistic creativity to deprived social groups. These multifarious practices formed a movement committed to a redefinition of the social role of art and to the advent of a genuine “cultural democracy” (Shelton Trust, Culture and Democracy : The Manifesto, 1k986). In the formulations that the movement developed in the 1970s and 1980s, this demand was inseparable from a radical political discourse of empowerment and challenge to traditional conceptions of culture. At a time when Cultural Studies were developing a critique of ideological hierarchies opposing high and low culture, the community art movement invested popular culture as a possible site of resistance against ideological domination. To study the community arts movement through the prism of the concept of commitment is an invitation to question the involvement of actors and the modes of implication of local populations in projects. At another level, the challenges raised by community arts practices went well beyond the artistic field and contributed to a political theory of culture: how did community arts combine the concepts of cultural expression and empowerment? Whereas the movement defined itself in terms of an ethics of collective action in the 1970s, what happened to this initial radicalism in the ideological context of the 1980s, characterised by the rise of individualistic and conservative values?